Letter - Nat. Soc operative printers & assistants, 6 May 1926 (page 2)
1926-05-06 "Letter - Nat. Soc operative printers & assistants, 6 May 1926 (page 2)" [g0610002.jpg], 6 May 1926, National Society of Operative Printers and Assistants